2020
DOI: 10.1093/nar/gkaa720
|View full text |Cite
|
Sign up to set email alerts
|

Locked nucleic acid building blocks as versatile tools for advanced G-quadruplex design

Abstract: A hybrid-type G-quadruplex is modified with LNA (locked nucleic acid) and 2′-F-riboguanosine in various combinations at the two syn positions of its third antiparallel G-tract. LNA substitution in the central tetrad causes a complete rearrangement to either a V-loop or antiparallel structure, depending on further modifications at the 5′-neighboring site. In the two distinct structural contexts, LNA-induced stabilization is most effective compared to modifications with other G surrogates, highlighting a potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 71 publications
1
16
0
Order By: Relevance
“…34,35 Also, a short G16 H8− G15 O5′ distance with a putative hydrogen bond interaction is suggested by the three-dimensional structures and matches with corresponding observations in several conventional Vshaped loop quadruplexes (Figure 7A). 33 The first TCTGA lateral loop stacks coaxially onto the Gcore with several NOE cross-peaks connecting T3/A7 residues with imino protons of the adjacent G-tetrad (Figure 4C and Figure S10A,C). Given a loop bridging a wide groove, an interfacial Watson−Crick AT base pair should easily be accommodated.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…34,35 Also, a short G16 H8− G15 O5′ distance with a putative hydrogen bond interaction is suggested by the three-dimensional structures and matches with corresponding observations in several conventional Vshaped loop quadruplexes (Figure 7A). 33 The first TCTGA lateral loop stacks coaxially onto the Gcore with several NOE cross-peaks connecting T3/A7 residues with imino protons of the adjacent G-tetrad (Figure 4C and Figure S10A,C). Given a loop bridging a wide groove, an interfacial Watson−Crick AT base pair should easily be accommodated.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In order to trace favorable and unfavorable contributions to V-loop formation, various sugar-modified G analogs have recently been introduced at specific positions of a (3+1) hybrid quadruplex, triggering rearrangements into a V-loop structure. [103][104][105] Detailed analysis of dual-modified V-loop quadruplexes bearing different combinations of G-analogs demonstrated that often overlooked sugar conformational preferences rather than glycosidic conformations were major contributors to V-loop stability. Thus, a stable V-loop structure was even formed when inserting LNA G with its fixed C3 0 -endo conformation (north) at the V-loop 5 0 -anchoring site to enforce a strongly disfavored syn conformation when followed by another 3 0 -flanking anti-LNA G. 105 On the other hand, a sugar pucker in the north domain for both 5 0 -and 3 0 -flanking residues seems to match backbone conformational requirements of a conventional 0 nt V-shaped loop (Fig.…”
Section: V-loop Quadruplexesmentioning
confidence: 99%
“…A second type of V-loop conformation has originally been suggested based on a sequence bearing a south/south-eastfavoring 2 0 -fluoro-arabinoguanosine analog at the 3 0 -flanking position. 104,105 In these alternative V-loop conformers, southpuckered residues are mostly found for both V-loop framing positions, allowing to differentiate V-shaped loops according to two distinct sugar conformational preferences (Fig. 16B, top).…”
Section: Reviewmentioning
confidence: 99%
“…The DNA primary sequence is a major factor determining the structure, and non-classical G4 structures may be formed depending on sequence, incorporating unusual elements such as a vacancy, [4][5][6][7] a bulge, 8 a very long loop, 9,10 unusual pairing schemes such as GCGC (or GAGA) quartets, [11][12][13] left-handed G4, 14,15 or guanine analogs. 16 In addition, the nature of the loops [17][18][19][20][21] and flanking sequences [22][23][24] contribute to structure and stability. Extrinsic stimuli include light, [25][26][27] temperature, 28 pH, 29 ligands, [30][31][32] crowding, 33 and metal ions.…”
Section: Introductionmentioning
confidence: 99%